Sunlight-Driven Photodegradation of RB49 Dye Using TiO2-P25 and TiO2-UV100: Performance Comparison - Zaaboul, Fatima; Canle, Moisés; Haoufazane, Chaimaa; Santaballa, Juan Arturo; Hammouti, Belkheir; Azzaoui, Khalil; Jodeh, Shehdeh; Hadjadj, Aomar; El Hourch, Abderrahim (Coatings, 2024)
By combining measurements of photocatalysis under solar irradiation with measurements of total organic carbon, we have compared the performance of two TiO2-based photocatalysts in the photodegradation of the dye Reactive Blue 49 (RB49). TiO2-P25 and TiO2-UV100 commercial photocatalysts were tested within a concentration ranging from 0.5 to 4 g/L. The dye solution concentration was varied from 10 to 50 mg/L and its pH was increased from 3 to 9. Extensive characterization of the photocatalysts was performed using Fourier-transform infrared spectroscopy, scanning electron microscopy and X-ray diffraction. TiO2-UV100 proved to be more active in adsorbing RB49 dye than TiO2-P25. At low dye concentrations, the adsorption equilibrium is reached in 15 min. This time increases to 1 h at higher concentrations. The photocatalytic degradation of aqueous RB49 under sunlight was monitored by UV-Vis spectrophotometry. The apparent rate constant of dye photodegradation with TiO2-UV100 is twice that of TiO2-P25. The total organic carbon (TOC) analysis showed a removal of around 98% with TiO2-UV100 and only 85% with TiO2-P25 after 3 h of solar irradiation. Over five photocatalytic cycles of 3 h, TiO2-UV100 maintained a more stable and higher efficient photocatalytic performance. All our results converge toward a better photocatalytic performance of TiO2-UV100 for the photodegradation of RB49 dye and indicate that the most decisive factor is its greater capacity to adsorb the pollutant.
Number: 10
Keywords: RB49; TiO_2; adsorption; photodegradation; solar photocatalysis; water treatment